2020
DOI: 10.1186/s12880-020-00513-z
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram to identify severe coronavirus disease 2019 (COVID-19) based on initial clinical and CT characteristics: a multi-center study

Abstract: Background To develop and validate a nomogram for early identification of severe coronavirus disease 2019 (COVID-19) based on initial clinical and CT characteristics. Methods The initial clinical and CT imaging data of 217 patients with COVID-19 were analyzed retrospectively from January to March 2020. Two hundred seventeen patients with 146 mild cases and 71 severe cases were randomly divided into training and validation cohorts. Independent risk factors were selected to construct the nomogram for predictin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Previous studies have suggested nomograms for predicting the risk of severe COVID-19 and COVID-19-related mortality using diverse laboratory findings, clinical features, and chest computed tomography (CT) findings. 15 16 17 18 19 24 25 In the present study, we considered age, sex, body mass index, symptoms at the time of COVID-19 diagnosis, and underlying diseases for the prediction model as these parameters can be obtained in the early clinical course. This can be very helpful for identifying patients at risk of mortality at the time of COVID-19 diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested nomograms for predicting the risk of severe COVID-19 and COVID-19-related mortality using diverse laboratory findings, clinical features, and chest computed tomography (CT) findings. 15 16 17 18 19 24 25 In the present study, we considered age, sex, body mass index, symptoms at the time of COVID-19 diagnosis, and underlying diseases for the prediction model as these parameters can be obtained in the early clinical course. This can be very helpful for identifying patients at risk of mortality at the time of COVID-19 diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“… 2 6 8 9 In other studies, laboratory or radiologic findings were included in the factors predicting severity or mortality associated with COVID-19. 15 16 17 18 19 However, data on these factors are available for a limited number of COVID-19 patients in clinical settings and it takes time to obtain the results of laboratory and radiological examinations, thereby delaying the prediction of mortality and severity in patients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…The independent predictors among CT signs were selected by using Chi-square test (or Fisher exact test), univariate and backward stepwise multivariate logistic regression methods [ 30 33 ]. Firstly, the CT signs with P-value less than 0.05 in Chi-square (or Fisher exact test) were retained to be further conducted with univariate and multivariate logistic regression.…”
Section: Methodsmentioning
confidence: 99%
“…9,10 Several studies have reported risk factors for severe COVID-19 such as demographics, symptoms, laboratory, and imaging findings. [5][6][7] Gong et al 5 found For personal use only. that old age, C-reactive protein, and lower albumin are associated with severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that Nomograms based on laboratory investigation, CT imaging, or immunological features can predict the progression to severe disease of COVID-19. [5][6][7] However, most of previous studies used only part of these data. Our objective was to establish a clinical nomogram combining clinical and imaging data to improve the accuracy of prediction.…”
Section: Introductionmentioning
confidence: 99%